Robust routing table design for IPv6 lookup - Yong, S. M.; Ewe, Hong Tat (IEEE Xplore, 2005)
The most pressing issue in IP lookup has been to solve the longest prefix match (LPM) problem. The solution must appeal to 3 major criteria of lookup and update performance of the routing table, and memory consumption. However, in IPv6 route table lookup addressing the problem of the possible long prefix (128-bit) in the worst case is crucial. In this study, this challenge is met by 'breaking' the address length into 'smaller' pieces of different prefix length in separate but contiguous tables. Coupled with smart prefix sorting and hardware hashing, this scheme is designed to be flexible and memory efficient.